2000
DOI: 10.1002/1521-4095(200010)12:20<1539::aid-adma1539>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transport in Fluorinated Copper-Phthalocyanine

Abstract: Air‐stable n‐type organic semiconductorswith high mobilities have been actively pursued since organic transistors have proven their importance in the development of low‐cost electronics. A promising candidate, fluorinated copper‐phthalocyanine, is investigated here. Electron transport properties are presented here for polycrystalline thin films and for single crystals of this compound, and it is reported that stable device performance in air can be achieved. The intrinsic transport mechanism is found to be ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…A value of approximately 10 12 cm Ϫ2 for n t is obtained from the experimental data ͑Fig. 11,19 Typical tunneling energies are in the range of several millielectron volts, which is in accordance with rough estimations. At low gate voltages E b is decreasing again.…”
Section: ͑2͒supporting
confidence: 83%
“…A value of approximately 10 12 cm Ϫ2 for n t is obtained from the experimental data ͑Fig. 11,19 Typical tunneling energies are in the range of several millielectron volts, which is in accordance with rough estimations. At low gate voltages E b is decreasing again.…”
Section: ͑2͒supporting
confidence: 83%
“…Compound 1 as a thin film shows mobility a factor of two lower [3] than the thin film of 3 and, thus, also makes a high quality film that captures a significant fraction of the available single-crystal mobility presumed from the analogous thin-film structure. However, the single-crystal structures cannot be considered optimal, since perfluorinated copper phthalocyanine, the only n-channel compound not highly sensitive to defects or otherwise unstable, [12] has a single-crystal mobility twice as high [13] as those observed for 3 and 4, and that of pentacene [10] and C 60 [14] is another three fold higher. It would be especially appealing to combine the solution and low temperature vapor processing of the NTCDI derivatives with higher electron mobility to produce idealized n-channel organic semiconductors.…”
mentioning
confidence: 99%
“…It has been reported that exposure of organic films including F 16 CuPc to various gaseous atmospheres affects the charge transport and the gap density of states [32]. Bussolotti et al have suggested that intermolecular disorder due to nitrogen and oxygen exposure increases drastically the gap DOS of pentacene [33].…”
mentioning
confidence: 99%
“…The differences between these two gap DOSs (values and energy) may be caused by different spatial distribution of HOMO and LUMO as already mention in Refs. [32,33]. In addition, a low density of gap states can reduce the band bending in the organic semiconductor at the gate-dielectric interface and thus increase the gate-bias-induced CPD shift.…”
mentioning
confidence: 99%